Constraints and Prospects of rice Production in a Climate Change Context in the Sissili Province, Burkina Faso - Sanou, Korotimi; Dipama, Jean-Marie (European Scientific Journal, ESJ, 2022)
In terms of irrigated agricultural production in Burkina Faso, rice is the second most important crop after maize. This rice production is supposed to satisfy domestic demand and reduce imports, which has an impact on the country’s trade balance. However, the rice sector is faced with climatic and technical productivity constraints. Indeed, the variability of temperatures and rainfall over the period 1988-2018, with its corollaries of drought and flooding episodes, has an impact on agricultural activity. The objective of this study is to analyze the effect of the dynamics of climatic parameters as well as the effectiveness of technological packages on rice productivity in Sissili Province. To this end, a methodology based on the quantitative approach was adopted. It is based on the collection, processing, and analysis of numerical data on key climatic parameters from the Pô synoptic station from 1988 to 2018. These data were correlated with those available on rice production over the same period. The analyses show that Sissili Province is marked by alternating rainfall deficits and surpluses, which have an impact on rice production, the evolution of which is out of phase with the increase in planted areas. This suggests that increasing the area planted seems to be an alternative way of compensating for a possible drop in rainfall. Under these conditions, the development of lowlands and water reservoirs represents opportunities for the diversification of production systems.